Peranan Radio Komunitas Agro dalam Pelayanan Informasi Pertanian di Desa Pangalengan - Teuku Winnetou (Pusat Penerbitan Universitas (P2U) LPPM Unisba, 2007)
The purpose of this research are to acknowledge the performance communication of radio, the role of radio and the constrains radio faces. The reseach wich implemented in Radio Komunitas Agro at Pangalengan Village used qualitative design with case study research method. The primery data collected with indeep interview from the respondents wich choice using snowball sampling technique. Informations and data collected were analized descriptively. The outcome of this research indicated, that: (1) generally, performance of sources, message, channel (tools and equipment), participation of users and communication effect of radio are getting from its own community. Especially, the messages are still domination of entertainment, tools and equipment used are still under the standard and still significantly are community which not access to radio transmissions; (2) Agro community radio have perseption by its hearer wich are positive, but not significant role in serving agricultural information for community; and (3) the constrains of the community radio are fund problems, facilities problems, management problems, human resource (announcer) problems, geographical conditions and supports from the local authority or asosiation.